2015
DOI: 10.1007/s13592-014-0345-7
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid enhances the immune response in Apis mellifera and contributes to the colony fitness

Abstract: -The primary food of adult honey bees (Apis mellifera ) is honey prepared by bees from nectar, provided by plants in order to stimulate the bee's pollination service. Nectar consists of carbohydrates, amino acids and water, as well as other minor compounds whose proportion varies among plant species and whose biological implications in the honey bee physiology require intense research. Several environmental stressors are causing the decline of bee colonies, and thereby, we tried to connect the nutritional qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 61 publications
8
63
0
Order By: Relevance
“…Abscisic acid, a phytohormone regulating physiological functions in plants, can be detected in nectar, honey and honeybees at all stages. This phytohormone enhances the immune response (cellular and humoral) and wound healing of individual worker honeybees and the colony (Negri et al 2015). Phytohormones are a new group of candidate substances that may be used by honeybees for various medicinal purposes.…”
Section: Honeymentioning
confidence: 99%
“…Abscisic acid, a phytohormone regulating physiological functions in plants, can be detected in nectar, honey and honeybees at all stages. This phytohormone enhances the immune response (cellular and humoral) and wound healing of individual worker honeybees and the colony (Negri et al 2015). Phytohormones are a new group of candidate substances that may be used by honeybees for various medicinal purposes.…”
Section: Honeymentioning
confidence: 99%
“…Lately, the role of naturally occurring compounds present in nectar, pollen, and honey is being revalued [14,15]. Through laboratory and field experiments, we have demonstrated that the supplementation of hives with syrup containing & 2017 The Author(s) Published by the Royal Society.…”
Section: Introductionmentioning
confidence: 99%
“…abscisic acid (ABA) enhanced the innate immune response of honeybees and the winter survival of the colony [15].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In insects, ABA ingested with nectar is detectable in honey bees and supplementation of hives enhanced would healing and immune cell activation in treated bees. 15 Mosquitoes similarly ingest a variety of bioactive factors during host feeding. In particular, human insulin and transforming growth factor beta in ingested blood can signal in the mosquito midgut to alter parasite infection.…”
Section: Introductionmentioning
confidence: 99%